Students' Difficulty with Newman's Analysis In Solving Hots Type Questions - Lusyana, Evvy; Istichomah, Istichomah (Al-Khawarizmi, 2024)
Abstract this study aims to determine the type of student error in solving Higher Order Thinking Skills (HOTS) type questions. using Newman analysis with indicators of Reading, Comprehension, Transformation, Process Skill, Encoding. This research uses a qualitative approach with a descriptive type of research. The subjects in the study amounted to 17 grade V students of SDN Mantingan 2. Data collection using test techniques using fractional material HOTS test questions conducted 2 times which were then analyzed using Newman Theory error analysis.        The results of research from 17 grade V students of SDN Mantingan 2 showed that there were student errors in Reading of 17.6%; Comprehension by 18.6%; Transformation by 20.5%; Process Skill by 45%; Encoding by 57.8%.